Organizational aspects of outpatient functional diagnostics - D. A. Tolmachev; I. M. Son; M. A. Ivanova; O. V. Reshetnikova (Кардиоваскулярная терапия и профилактика)
The high cardiovascular morbidity and the use of modern research methods in practice, the high demand for functional research with the workload growth of specialists due to modern requirements, including the work with medical documentation, indicate the need for organizational changes.Aim. To identify organizational problems of functional medicine practitioners work and determine ways to solve it.Material and methods. Using descriptive statistics, the analysis of federal statistical observation № 30 “Data on medical organization” was carried out. It characterizes the work of functional medicine practitioners in subjects of the Russian Federation in 2012-2017, as well as their photo and time tracking research.Results. The data of federal statistical observation showed that the lowest workload of practitioners was noted in the North-West Federal District, where the growth in the number of testing procedures per specialist occurred by 14,5%. To a lesser extent, this parameter increased in the Central Federal District — by 12,6%. The Volga Federal District takes the second place: the number of testing procedures increased by 21,8%. The highest growth was noted in the Siberian Federal District. By carrying out photo and time tracking research, the weighted-average costs of working time for conducting functional tests are established taking into account the type of test. It will help to reduce the burden of specialists.Conclusion. The results of the study showed an increase in the number of functional tests by 15,9%. A higher burden in the work of functional medicine practitioners was noted in the Penza Region, the Chukotka Autonomous Okrug, the Republic of Ingushetia and the Kirov Region. The formation of document on the norms of time for conducting functional tests, based on the results of photo and time tracking research and its implementation will help to reduce the burden of specialists.